Rogue lawyer - Grisham, John (New York : Doubleday, a division of Penguin Random House, LLC, 2015)
Sebastian Rudd is not your typical street lawyer. He works out of a van, he has no firm, and only one employee, his driver, whos also his bodyguard, law clerk, confidant, and golf caddy.
Keywords: Criminal defense lawyers -- Fiction; Teenagers with mental disabilities -- Fiction; Girls -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Judicial ethics -- Fiction; Legal stories; Suspense fiction